The Roma: a Minority in Europe - Roni Stauber, Raphael Vago (Central European University Press, 2007)
The main issues arising from the encounter between Roma people and surrounding European society since the time of their arrival in Medieval Europe until today are discussed in this work. The history of their persecution and genocide during the Nazi era, in particular, is central to the present volume. Significantly, some authors sought to emphasize the continuing history of prejudice and persecution, which reached a peak during the Nazi era and persisted after the war. Current questions of so...